Mechanical and thermal properties of polyurethane/neoprene/ graphene blends - A, Syahir; M B, Mat Piah; Waleed, Alhadadi; F, Hafidzah; M S Z, Desa; M Z M, Noor; Muhammad Aliff Nazreen, Norazmi; A., Ramli (IOP Publishing Ltd, 2020)
This work investigated the properties of the polyurethane/neoprene/graphene nanocomposites blends specifically in mechanical and thermal aspects for solid ankle cushion heel (SACH) foot in the prosthetic application. The aim of this work was to study the effect of neoprene and graphene contents in mechanical and thermal properties of polyurethane/neoprene/graphene blends. Polyurethane is one of the most frequently used polymers in the medical devices, footwear, automotive and construction industries. Polyurethane which is high mechanical strength, high thermal withstands and flexibility was blended with the additives, neoprene and graphene to reduce the rigidity and enhances the mechanical properties for a prosthetic foot. A solution mixing method was used to prepare the samples with different formulations of polyurethane, neoprene and graphene. The samples were analyzed and characterized in terms of mechanical, thermal and morphology properties. The result shows that the optimum composition blended with 97 wt% polyurethane, 2 wt% neoprene and 1 wt% graphene. The sample possesses high tensile strength (14.38 MPa) and high Young’s modulus (1.11 MPa), high thermal stability, elastic and flexible. The use of a low amount of graphene in polyurethane and neoprene blend has been demonstrated to enhance the mechanical and thermal properties of the nanocomposites.